HUBUNGAN KREATIVITAS BELAJAR DAN MINAT BELAJAR TERHADAP HASIL BELAJAR SISWA MATA PELAJARAN DASAR LISTRIK DAN ELEKTRONIKA - Dewi Novita; Rosnelli . (Universitas Negeri Medan, 2022)
Abstract This study aims to determine: (1) the relationship of learning creativity to student learning outcomes in basic subjects of electricity and electronics; (2) the relationship of interest in learning to student learning outcomes in the basic subjects of electricity and electronics; (3) the relationship between learning creativity and interest in learning to student learning outcomes in basic electrical and electrical subjects.The research method used is ex post facto. The population in this study amounted to 210 respondents with a sample of 138 respondents who were taken through the Simple Random Sampling technique. The results of this study indicate that: 1) There is a positive and significant relationship between learning creativity and student learning outcomes as indicated by the value (tcount > ttable) which is 8.736 > 1.9773. The magnitude of the effective relationship between learning creativity is 29.8%. 2) There is a positive and significant relationship between interest in learning and learning outcomes as indicated by the value (tcount > ttable) which is 8.354 > 1.9773. The magnitude of the effective relationship of interest in learning is 26.4%. 3) There is a positive and significant relationship between learning creativity and interest in learning together on learning outcomes of 56.2% while 43.8% is influenced by other variables not examined. This is indicated by the value (Fcount > Ftable) which is 57.100 > 3.06. Keywords: Learning Creativity, Learning Interest, Learning Outcomes AbstrakPenelitian ini bertujuan untuk mengetahui: (1) hubungan kreativitas belajar terhadap hasil belajar siswa dalam mata pelajaran dasar listrik dan elektronika; (2) hubungan minat belajar terhadap hasil belajar siswa dalam mata pelajaran dasar listrik dan elektronika; (3) hubungan kreativitas belajar dan minat belajar terhadap hasil belajar siswa dalam mata pelajaran dasar listrik dan elektronika.Metode penelitian yang digunakan yaitu ex post facto. Populasi dalam penelitian ini berjumlah 210 responden dengan sampel sebanyak 138 responden yang diambil melalaui teknik Simple Random Sampling. Hasil dari penelitian ini menunjukkan bahwa: 1) Ada hubungan positif dan signifikan antara kreativitas belajar dengan hasil belajar siswa yang ditunjukkan dengan nilai (thitung > ttabel) yaitu 8,736 > 1,9773. Besarnya hubungan efektif kreativitas belajar sebesar 29,8%. 2) Ada hubungan positif dan signifikan antara minat belajar dengan hasil belajar yang ditunjukkan dengan nilai (thitung > ttabel) yaitu 8,354 > 1,9773. Besarnya hubungan efektif minat belajar sebesar 26,4%. 3) Ada hubungan positif dan signifikan antara kreativitas belajar dan minat belajar secara bersama-sama terhadap hasil belajar sebesar 56,2% sedangkan 43,8% dipengaruhi oleh variabel lain yang tidak diteliti. Hal ini ditunjukkan dengan nilai (Fhitung > Ftabel) yaitu 57,100 > 3,06. Kata Kunci : Kreativitas Belajar, Minat Belajar, Hasil Belajar